Analysis Trend Research Smart Learning Environment Framework - Rivaldi Rizalul Akhsan; Dana Indra Sensuse (Eduvest - Journal of Universal Studies, 2025)
Technology has brought a huge impact in the field of education. Technology in the field of education not only includes online learning resources, but also involves the concept of Smart Learning Environment (SLE). SLE in the world of education is increasingly influential along with the evolution of modern learning needs. The challenge to realize SLE as a whole is that there is no reference that is a standard in the application and evaluation of technology in the educational environment. Currently, there is still no data on standards or frameworks detailing the use of technology in education. So the purpose of this study is to focus on exploring the trend of the framework in the Smart Learning Environment (SLE) to see what kind of related research can provide future research recommendations. This study uses a systematic literature review approach from 27 final articles. The results of this research found that many studies conducted case studies at the university level. In addition, the research discusses a lot about the performance evaluation of the implementation of existing systems. On the other hand, some research focuses on too general and lacks a teacher's perspective. So that in the future, this study recommends research that explores specifically on certain aspects such as providing practical guidance to increase learning effectiveness and providing recommendations for improvement and development that can ensure that the learning process remains relevant and responsive to the demands of the times.